Analyzing the impact of oil price fluctuations on the Moroccan stock market: A Multifractal Detrended Cross-Correlation Approach - BENBACHIR , Soufiane (Revue Internationale des Sciences de Gestion, 2025)
This study investigates the multifractal characteristics of cross-correlations between the Brent crude oil market and the Moroccan stock market, focusing on both the overall MASI index and its sector-specific MASI Oil index, using the Multifractal Detrended Cross-Correlation Analysis (MF-DCCA). Initial findings from the Cross-Correlation Significance Test and the DCCA Cross-Correlation Coefficient indicate persistent cross-correlations between the Brent crude oil market and both the MASI and MASI Oil indices, suggesting that shocks in the Brent market may exert lasting effects on these indices. These findings challenge the assumptions of market independence under the Efficient Market Hypothesis (EMH). Further analysis using MF-DCCA components, including the Generalized Hurst exponents, Rényi exponents, and Hölder Singularity Spectrum, reveals long-range persistent cross-correlations and multifractal characteristics in both pairs. Notably, the Brent–MASI pair displays stronger multifractality, indicating more persistent and potentially more volatile dynamics. Moreover, surrogate and shuffling transformations revealed that the multifractal nature of these cross-correlations is driven by long-term dependencies and heavy-tailed distributions. This study demonstrates the effectiveness of multifractal models in capturing the complex, non-linear, and long-range cross-correlations between oil prices and the Moroccan stock market. Nonetheless, the absence of high-frequency data limits the ability to analyze short-term market fluctuations.